STABILITAS ANTIOKSIDAN EKSTRAK KAYU SECANG (Caesalpinia sappan L) SELAMA PENYIMPANAN - , ATIK ERNAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Secang (Caesalpinia sappan) is one of the plant material that is commonly used as a natural dye for food, drinks and a potential source of natural antioxidants. Antioxidant activity in secang wood, due brazilin compounds, flavonoids and phenolic contains. Extract storage secang wood is usually in the form of solutions and powders. Publications so far on the effect of temperature on the antioxidant activity of secang wood is still limited. Therefore, this study aims to determine the stability of the antioxidant extract secang wood in the form of solutions and powders during storage. The research was conducted by using a solvent to extract secang wood water. After it was filtered and dried by freeze dryer. Secang wood extract stored into two forms namely liquid (temperature 10oC, 20oC, 30oC, 40oC, 50oC) and powder (temperature 10oC, 20oC, 30oC) and tested on days 0, 4, 8, 12 , 16, and 20. The parameters tested include testing antioxidant activity by DPPH radical scavenging, total phenols, flavonoids and vitamin C. Antioxidant activity and flavonoid extract solution and powder secang wood The higher the temperature and the longer the storage, the antioxidant activity of extracts secang wood in the form of a solution or powder that fell in line with decreased levels of total phenolics, flavonoids and vitamin C. showed a significant decrease with the higher temperatures and the length of storage time. While vitamin C powder extract solution and secang wood showed no significant decrease. The total phenolic extract powder secang wood relatively stable until day 16, at 10, 20, and 30oC although tends to fall. For that, recommended storage for secang wood extract in the form of powder.